2019
DOI: 10.14744/etd.2019.26779
|View full text |Cite
|
Sign up to set email alerts
|

The impact of lymphovascular invasion on recurrence-free survival in high-risk stage II colorectal cancer patients treated with adjuvant therapy.

Abstract: Objective: Lymphovascular invasion (LVI) may affect disease recurrence after operation for colorectal cancer (CRC). Whether LVI is an exact prognostic variable remains uncertain. This research aimed to investigate the relationship between clinicopathologic factors, disease-free survival (DFS), and overall survival (OS) in patients with high-risk stage II colon cancer who underwent adjuvant treatments, focusing on LVI. Materials and Methods: This study retrospectively investigated 173 patients who underwent ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This study aimed to identify possible preoperative factors likely to be associated with LVI in CRC. Studies have indicated that LVI is present in 5.2% to 89.5% of patients, depending on the CRC stage [17][18][19][20][21]. In our study, this proportion was 53.13%, which is consistent with the literature.…”
Section: Discussionsupporting
confidence: 92%
“…This study aimed to identify possible preoperative factors likely to be associated with LVI in CRC. Studies have indicated that LVI is present in 5.2% to 89.5% of patients, depending on the CRC stage [17][18][19][20][21]. In our study, this proportion was 53.13%, which is consistent with the literature.…”
Section: Discussionsupporting
confidence: 92%
“…However, the TNM stage alone does not accurately predict the prognosis and distinguish whether the patient should receive adjuvant chemotherapy, particularly in patients with stage II CRC. Among CRC, TNM stage II constitutes a very wide spectrum and the 5-year overall survival of surgically resected patients ranges between 75 and 80% [3][4] . Plenty of clinicopathological features have been associated with a high risk of recurrence and metastasis in stage II CRC, among which perineural invasion (PNI) has been associated with a poor outcome [5][6][7] and the postoperative survival rate of stage II CRC patients with PNI was supposed to be more similar to that of stage III [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Among CRC, TNM stage II constitutes a very wide spectrum and the 5-year overall survival of surgically resected patients ranges between 75% and 80%. 3,4 Plenty of clinicopathological features have been associated with a high risk of recurrence and metastasis in stage II CRC, among which perineural invasion (PNI) has been associated with a poor outcome and the postoperative survival rate of stage II CRC patients with PNI was supposed to be more similar to that of stage III. [5][6][7][8] Complex signaling between tumor cells, the nerves, and stromal cells is probably related to the pathogenesis of PNI.…”
Section: Introductionmentioning
confidence: 99%